UPAYA MENINGKATKAN KETRAMPILAN MERANGKAI BUNGA FLANEL PADA ANAK TUNAGRAHITA RINGAN DI SLB DAMAYANTI - Agoestin Kemalawati (Jurnal Abdimas Akademika, 2020)
ABSTRACT This community service activity aims to assist assistance in improving the skills of making patterns, making flowers and leaves, arranging according to the theme and shape of flannel flower arrangements for mentally retarded children in preparation for the LKS-ABK competition. The implementation of community service is carried out at SLB Damayanti. The method used in this community service is the demonstration method with a personal approach and personal assistance. Implementation of assistance is 5 times with details, namely; introducing theory according to the LKS-ABK technical guidelines, making flower and leaf patterns, learning to string and the final stages of practicing all stages of making patterns, making flowers and leaves, arranging according to the competition technical guidelines. The results of the mentoring activities are (1) students are able to make patterns, make flowers and leaves, arrange according to the theme and shape; (2) students feel more ready to compete because they already have confidence and know how much they are capable.